Estágio curricular supervisionado na licenciatura em Matemática: um componente curricular em discussão - Zimmer, Iara (2017)
The mentored curricular internship required of students attending undergraduate teaching certification programs in mathematics in Brazil was selected as the focus of this investigation. The internship is a field of experience where teacher training can be integrated with the social setting in which educational practices take place, thus constituting a crucial period in the training of teachers, providing them with the opportunity to experience the school context and expand the heterogeneous nature of learning acquisition in terms of teaching practices, enabling mathematics students to develop knowledge and skills. Drawing on classroom observations and practices, these students are led to reflect on what teaching consists of and how mathematics should be taught—essential elements in building their professional identities. The fact that this is not currently the predominant conception of internship within teaching certification programs prompted this investigation, as did the dearth of studies on how this type of internship actually occurs in these programs. The theoretical framework that guided the analysis addressed the educational legislation, teacher training, training of future mathematics teachers, and mentored curricular internships. Under a qualitative research approach, the study entailed the analysis of pedagogical projects of teaching certification programs in mathematics offered at five federal universities, one from each Brazilian region. Seven internship mentors and 20 interns were interviewed. Data interpretation drew on elements of Laurence Bardin‘s content analysis. Broadly, the mentored curricular internship was found to approach the conception of internship as a space where theory and practice, in interconnection with school contexts, promote, with the contribution of teachers‘ experience, the construction of learning about school-based education and teaching. Most of the pedagogical projects investigated reported that internship format had been remodeled to comply with changes in legislation—an aspect also highlighted by interviewees. However, both mentors and interns reported a lack of coordination between teaching certification programs and internships, which causes internship success to hinge on the efforts of teachers, or groups thereof—whether serving at departments of mathematics or schools of education—who are aware of their own roles as trainers of future teachers. Mentors pointed out that recent discussions and new norms have not translated to changes in the actual functioning of teaching certification programs, still largely founded on a theory-based focus typical of non-teaching bachelor degree programs. While teaching certification programs in mathematics continue to be shaped after this model, faculty members will be unable to give the mentored curricular internship as much value as they have assigned to more theoretical curricular components. As a result, internships tend to remain disconnected, and their importance as a formative period will continue to depend on individual efforts, resulting in typically slow changes to the structure of teaching certification programs in mathematics